2019
DOI: 10.1093/jamia/ocy183
|View full text |Cite
|
Sign up to set email alerts
|

Can laypeople identify a drug-induced QT interval prolongation? A psychophysical and eye-tracking experiment examining the ability of nonexperts to interpret an ECG

Abstract: Objective The study sought to quantify a layperson’s ability to detect drug-induced QT interval prolongation on an electrocardiogram (ECG) and determine whether the presentation of the trace affects such detection. Materials and Methods Thirty layperson participants took part in a psychophysical and eye-tracking experiment. Following training, participants completed 21 experimental trials, in which each trial consisted of 2 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For examples, as predictors of driving performance, the stationary gaze entropy (SGE) and gaze transition entropy (GTE) are used to improve the regression and classification model in alcohol and sleep conditions [12, 13]. Not only in driving tasks, while craft-workers and doctors were performing their specific tasks, whose eye-movement strategies is also tightly relevant to the goal that to be achieved [14, 15]. So, it is meaningful to explore the law of cognitive process of these specific skills in future work.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, as predictors of driving performance, the stationary gaze entropy (SGE) and gaze transition entropy (GTE) are used to improve the regression and classification model in alcohol and sleep conditions [12, 13]. Not only in driving tasks, while craft-workers and doctors were performing their specific tasks, whose eye-movement strategies is also tightly relevant to the goal that to be achieved [14, 15]. So, it is meaningful to explore the law of cognitive process of these specific skills in future work.…”
Section: Introductionmentioning
confidence: 99%
“…From a perceptual-cognitive perspective, this may be related to the fact that people are poor at perceiving quantity represented along a horizontal scale [ 47 49 ]. Research has also shown that changes in the T-wave morphology and/or artifacts in the ECG signal can cause misinterpretation of the QT-interval length [ 40 , 41 , 50 , 51 ]. The effect of heart rate on the QT-interval is another challenge, as it is the proportionate rather than absolute length that is important, and it is common to misinterpret the QT-interval at heart rates that differ from the ‘standard’ 60 bpm [ 52 ].…”
Section: Introductionmentioning
confidence: 99%